Ferromagnetic Bismuth-Substituted CeO2 Nanostructures and Prevalence of Antiferromagnetic Clusters - Alla S.K.; Meena S.S.; Gupta N.; Mandal R.K.; Prasad N.K. (My University, 2025)
Bismuth-substituted CeO2 (Bi0.05Ce0.95O2) nanostructured material have displayed room temperature ferromagnetic behavior. The substitution of Ce ions with Bi3+ ions decreased the saturation magnetization (MS) value of CeO2. UV-Vis and photoluminescence spectroscopic analyses revealed the occurrence of defect states i.e. surface oxygen vacancies in the sample, which facilitated ferromagnetic interactions in the Bi-substituted CeO2 nanostructures. Further, the clusters in the sample could provide antiferromagnetic interaction amongst ions, which reduced the MS value of CeO2. The clusters in the annealed sample was substantiated from its ZFC/FC curve. X-ray photoelectron spectroscopy analysis revealed the presence of Bi3+, Ce3+, and Ce4+ ions in the sample. High-resolution transmission electron microscopy (HRTEM) images suggested the spherical and rod-shaped morphology for the particles. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.